2003
DOI: 10.1016/s0014-5793(03)00875-5
|View full text |Cite
|
Sign up to set email alerts
|

Lipid peroxidation in skeletal muscle of obese as compared to endurance‐trained humans: a case of good vs. bad lipids?

Abstract: Intra-myocellular triglycerides (IMTG) accumulate in the muscle of obese and endurance-trained (ET) humans and are considered a pathogenic factor in the development of insulin resistance, in the former. We postulate that this paradox may be associated with the peroxidation status of the IMTG. IMTG content was the same in the obese and ET subjects. The lipid peroxidation/IMTG ratio was 4.2-fold higher in the obese subjects. Hence, obesity results in an increased level of IMTG peroxidation while ET has a protect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
127
2
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(140 citation statements)
references
References 13 publications
10
127
2
1
Order By: Relevance
“…As elevated IMTG accretion in type 2 diabetic patients is the result of a structural imbalance between NEFA uptake, IMTG deposition and its subsequent mobilisation and/or oxidation [21][22][23], it has been suggested that an elevated IMTG turnover rate can prevent excessive accumulation of intramyocellular FA metabolites [9, 10, 13-16, 44, 45] and/or reduce the degree of intramyocellular lipid peroxidation [17]. In agreement, interventions known to Fig.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…As elevated IMTG accretion in type 2 diabetic patients is the result of a structural imbalance between NEFA uptake, IMTG deposition and its subsequent mobilisation and/or oxidation [21][22][23], it has been suggested that an elevated IMTG turnover rate can prevent excessive accumulation of intramyocellular FA metabolites [9, 10, 13-16, 44, 45] and/or reduce the degree of intramyocellular lipid peroxidation [17]. In agreement, interventions known to Fig.…”
Section: Discussionmentioning
confidence: 66%
“…More recent insights from various lipid infusion studies have led to an alternative mechanism [9][10][11][12][13]. The latter suggests that elevated NEFA delivery and/or impaired FA oxidation result in intramyocellular accumulation of triacylglycerol (TG) and FA metabolites (such as fatty acyl-CoA, ceramides and diacylglycerol), which induce defects in the insulin signalling cascade, causing skeletal muscle insulin resistance [9,10,[13][14][15][16][17]. Insulin resistance can subsequently lead to development of the hyperglycaemic and/or hyperinsulinaemic state that is associated with type 2 diabetes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…29 Furthermore, an increase in IMTGs has been shown in insulin-resistant obese and Type 2 diabetics, when compared with lean subjects. 3,9 Goodpaster et al 3 found that the IMTG content, measured using a routine Oil red oil stain, correlated with insulin sensitivity in lean, obese and type 2 diabetic subjects. Perseghin et al 30 reported that IMTG, quantified using magnetic resonance spectroscopy (MRS), in offspring of Type 2 diabetic patients correlated with insulin resistance.…”
Section: Association Between Insulin Resistance and Imtg Contentmentioning
confidence: 99%
“…Elevated fatty acid delivery and/or impaired fatty acid oxidation result in net intramyocellular accumulation of triacylglycerol and fatty acid metabolites (such as fatty acyl-CoA, ceramides and diacylglycerol). The latter are likely to induce defects in the insulin signalling cascade, thus causing insulin resistance [4][5][6][7][8][9][10] in skeletal muscle.…”
Section: Introductionmentioning
confidence: 99%